Mutagenicity of 4-nitroquinoline l-oxide and three hair dye components in Sordaria brevicollis - C. C. Yu-Sun; L. A. Carter; L. Sandoval; A. Thompson (Fungal Genetics Reports, 1981)
Mutagenicity of 4-nitroquinoline 1-oxide and three hair dye components in Sordaria brevicollis